Underwater Remotely Operated Vehicle Control System Ar-chitecture - Imam Sutrisno; Yuning Widiarti; Projek Priyonggo; Tri Mulyatno Budhi Hartanto; Ari Wibawa Budi Santosa; Faris Nofandi; Monika Retno Gunarti; Agus Prawoto; Anak Agung Istri Sri Wahyuni (Indonesian Journal of Innovation Multidisipliner Research, 2024)
Underwater Remotely Operated Vehicle (ROV) control system architecture, work Class II - underwater inspection is demonstrated. The object is programmed on MATLAB simulink. The nonlinear modeled plants were processed by approximation way. Author planned a controller of an underwater ROV object. PID controller is used modeled plant. Tuning PID tool is used MATLAB for choose underwater ROV controller. Researchers tested an underwater ROV for system and solving problems an underwater ROV architecture.